2012
DOI: 10.1099/jmm.0.044115-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characteristics of one highly multi-drug-resistant strain of Klebsiella ozaenae

Abstract: One highly multi-drug-resistant, mucus-producing and foul-smelling strain of Klebsiella ozaenae was isolated from a patient in the ICU of a Chinese tertiary hospital. MICs of several clinical antimicrobials against the strain were obtained using the Vitek-2 Compact System with AST-GN13 cards and resistance genes were evaluated by PCR and gene sequencing. The strain was resistant to most of the b-lactams and quinolones tested and carried several antibiotic resistance genes, including bla KPC-2 , bla TEM-98 , bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Huang et al reported one highly multi-drug -resistant strain of K. ozaenae which was isolated from an ICU patient and resistant to most of the tested antimicrobials, including imipenem, ertapenem, ampicillin/sulbactam, piperacillin-tazobactam, aztreonam, ceftazidime, cefepime, levofloxacin and ciprofloxacin, but it was sensitive to gentamicin. 10 Abbas et al reported similar results: in their study, the K. ozaenae isolate was multi-resistant to most tested antibiotics, including amoxicillin, cephalothin, ceftazidime, cefotaxime, amikacin, tetracycline, naldixic acid, erythromycin and trimethoprim, but it was sensitive to imipenem and gentamicin. 11 In another cross-sectional retrospective study, performed by Radji et al, the authors collected specimens from 385 patients, of which 249 (64.68%) were cultured positive, including 21 that were positive for K. ozaenae.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Huang et al reported one highly multi-drug -resistant strain of K. ozaenae which was isolated from an ICU patient and resistant to most of the tested antimicrobials, including imipenem, ertapenem, ampicillin/sulbactam, piperacillin-tazobactam, aztreonam, ceftazidime, cefepime, levofloxacin and ciprofloxacin, but it was sensitive to gentamicin. 10 Abbas et al reported similar results: in their study, the K. ozaenae isolate was multi-resistant to most tested antibiotics, including amoxicillin, cephalothin, ceftazidime, cefotaxime, amikacin, tetracycline, naldixic acid, erythromycin and trimethoprim, but it was sensitive to imipenem and gentamicin. 11 In another cross-sectional retrospective study, performed by Radji et al, the authors collected specimens from 385 patients, of which 249 (64.68%) were cultured positive, including 21 that were positive for K. ozaenae.…”
Section: Discussionmentioning
confidence: 60%
“…ozaenae is sensitive or intermediately sensitive to antimicrobials including cotrimoxazole, cephalosporins, quinolones, tetracyclines and aminoglycosides; however, which kind of antimicrobial to use in the treatment of K. ozaenae infections remains uncertain due to drugresistance. 10 Therefore, an antibiotic susceptibility test should be performed before treatment to guide the antimicrobials use. Huang et al reported one highly multi-drug -resistant strain of K. ozaenae which was isolated from an ICU patient and resistant to most of the tested antimicrobials, including imipenem, ertapenem, ampicillin/sulbactam, piperacillin-tazobactam, aztreonam, ceftazidime, cefepime, levofloxacin and ciprofloxacin, but it was sensitive to gentamicin.…”
Section: Discussionmentioning
confidence: 99%
“…Species were further identified using an automated mass spectrometry microbial identification system (MALDI-TOF, Bruker, USA) and re-confirmed by 16S rRNA, RecN , and Hsp60 sequencing (Hoffmann and Roggenkamp, 2003 ; Ribeiro et al, 2015 ). Common carbapenemase-encoding genes, including bla KPC , bla NDM , bla VIM , bla IMP , bla GES , bla SME , bla IMI , bla SIM , bla GIM , bla SPM , bla OXA−23 , bla OXA−24 , and bla OXA−58 , from all 156 isolates were amplified, and amplicons were sequenced (Pfeifer et al, 2010 ; Huang et al, 2012 ; Zhang et al, 2017 , 2018 ). Plasmids of the untypeable incompatibility group, represented by pCKPC18-1 (CP022276), were screened by specific primers (UTF-TGCATCGATACGTTCCTGCA and UTR-ACTCGCTAGCATGGAACATC) targeting the replication initiator ( repA ).…”
Section: Methodsmentioning
confidence: 99%
“…A total of 13 carbapenemase-encoding genes, bla KPC , bla NDM , bla VIM , bla IMP , bla SME , bla GES , bla IMI , bla SIM , bla SPM , bla GIM , bla OXA-23 , bla OXA-24 and bla OXA-58 , from all the K. pneumoniae strains were amplified and sequenced [3,4,15,16]. The bla KPC genetic structures were detected by PCR as described in our previous study [8].…”
Section: Detection Of Resistance and Virulence Genesmentioning
confidence: 99%